Generalized sasakian-space-forms with D-conformal curvature tensor - Shah, Riddhi Jung (Kathmandu University Journal of Science Engineering and Technology, 2013)
In this paper we study generalized Sasakian-space-forms with D-conformal curvature tensor. In generalized Sasakian-space-forms, we investigate some results on D-conformally flat, ?-D-conformally flat, ?-D-conformally flat and the curvature condition B(? ?).S=0. Kathmandu University Journal of Science, Engineering and Technology Vol. 8, No. II, December, 2012, 48-56